Simulation Analysis of Void Defect Detection in Sandwich-Structured Immersed Tunnel Using Elastic Wave - Ruiqiang Liu; Songhui Li; Guoxin Zhang; Shenyou Song; Jianda Xin (Shock and Vibration)
Void defects can be easily generated between a steel plate and concrete joint due to the complicated internal structure of a sandwich-structured immersed tunnel (SSIT), which affect the overall bearing capacity of the main structure of the immersed tube tunnel. A prototype experiment was conducted to study the application of impact imaging method in the nondestructive detection of void defects in SSITs. The detection criterion for the impact imaging method was established based on the features of the waveform data. Nevertheless, the influence of steel plate thickness, material properties, void location, and structure on the detection accuracy of the impact imaging method is unclear. Therefore, numerical simulation was applied to study the influencing factors by establishing a different condition model. Good agreement between the experimental and numerical results was observed for the response waveform collected from the inspection area. Using the calculation model and identified material parameters validated in the active prototype experiment, numerical simulations of several sets, which considered all influencing factors, were performed. The application scope and sensitivity of the impact image method were recommended to reduce misjudgement in practical applications and improve detection accuracy.